TQM modern example for the management of the organizations contemporary - theoretical entrance - - kaf, moussa; belkhiri, mourad (Journal of Social Sciences and Humanities, 2020)
This article is due to the increasing interest in administrative work and the organization's management specially, the spread of Total Quality Management style in many developed societies, and the imperative of keeping goods and services in line with international specs and standards, with the aim of continuously improving quality, meeting and exceeding the users' tastes. Therefore, the objective of the total quality management is to seek quality in all its meanings and apply it in various aspects of institutional work, from identifying the needs of consumers and customers to knowing the satisfaction of the beneficiary of the various services or products provided to him, and to doing the job and completing the tasks by human resources in the best possible way, with the best possible method, and desired quality... So,TQM is one of the Total Management models in the modern management of organizations, which are widely known in the field of institutional work; it has had a considerable resonance and applicability in global economic institutions and firms. This model based on the talents and capabilities of both management and staff to continuously improve quality and productivity by using teams to meet consumer needs, both in terms of quality, speed of delivery, value and quality. TQM is an enterprise management philosophy in which both consumer needs are met and project objectives are met. Given the prestige of this modern management model, this article comes as an attempt to learn how TQM has emerged, its most prominent pioneers and achievements, identifying the concept and identifying the most important tariff classifications forcomprehensive quality management and its stages of development, as well as its tasks, with a focus on the components of Total quality management and the principles that Deming presents as a model. And finally, the benefits, disadvantages and most important steps to improve overall QM.